2020
DOI: 10.1108/aeds-02-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

Migration and sustainable development in Thailand

Abstract: Purpose Previous studies have focused on migration and development from an economic perspective. The purpose of this paper is to evaluate sustainable migration and development in an integrative manner, including economic, social and environmental perspectives linking theoretical frameworks with empirical evidence in Thailand. Design/methodology/approach A framework of migration and sustainable development was developed in a structured and integrative manner, and the shift in migration and development pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…A few studies argue the reasonable drivers of the free flow of skilled labour migration policies in CLMV countries (Jones, 2016; Chao, 2017; Jurje and Lavenex, 2018; Chamaratana and Daovisan, 2019; Pholphirul, 2019; Daovisan and Chamaratana, 2020; Gerard and Bal, 2020). Current studies (Ullah et al , 2019) focus on skill deficiencies in receiving countries (Kampan and Tanielian, 2017; Bhula-or, 2021) and the inflow to Thailand (Kaur, 2010; Nguyen, 2013; Arisman and Jaya, 2021), especially from low-income (e.g. Philippines, Indonesia, Myanmar and Vietnam) to high-income countries (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies argue the reasonable drivers of the free flow of skilled labour migration policies in CLMV countries (Jones, 2016; Chao, 2017; Jurje and Lavenex, 2018; Chamaratana and Daovisan, 2019; Pholphirul, 2019; Daovisan and Chamaratana, 2020; Gerard and Bal, 2020). Current studies (Ullah et al , 2019) focus on skill deficiencies in receiving countries (Kampan and Tanielian, 2017; Bhula-or, 2021) and the inflow to Thailand (Kaur, 2010; Nguyen, 2013; Arisman and Jaya, 2021), especially from low-income (e.g. Philippines, Indonesia, Myanmar and Vietnam) to high-income countries (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that network capital is associated with chain, social, human and financial networks. The findings have filled the theoretical gaps in network capital research (Bhula-or, 2021;Daovisan et al, 2022;Statham et al, 2020;Suhardiman et al, 2021;Vigneswaran, 2020). This research is one of the few studies in existing…”
Section: Theoretical Contributionsmentioning
confidence: 79%
“…Building on the network capital concept, Koltai et al (2020) typically framed it as encompassing human, financial, social and chain migration. The presence of network capital in family SMEs has been associated with strong ties, interpersonal connections, agent networks and employer links (Baù et al , 2021; Bhula-or, 2021; Boateng et al , 2019; Hajro et al , 2021; Godin and Don, 2021; Kalmijn, 2022). This network capital analyses three levels forming migrant network capital in family SMEs: individual level (self-migrant), agent level (group migrant) and national level (Memorandum of understanding migrant) (Christ, 2020; Leal and Harder, 2023; Moret, 2020).…”
Section: Theoretical Lens and Contextmentioning
confidence: 99%
See 2 more Smart Citations